2003
DOI: 10.1046/j.1460-9568.2003.02789.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered responses to orexigenic (AGRP, MCH) and anorexigenic (α‐MSH, CART) neuropeptides of paraventricular hypothalamic neurons in early postnatally overfed rats

Abstract: Food intake and energy expenditure are regulated by neuropeptides in the hypothalamus. While cocaine- and amphetamine-regulated transcript (CART) peptide and melanocortins such as alpha-melanocyte-stimulating hormone (alpha-MSH) are anorexigenic and increase energy expenditure, the endogenous melanocortin receptor antagonist agouti gene-related protein (AGRP), melanin-concentrating hormone (MCH) and neuropeptide Y (NPY) are orexigenic, anabolic peptides. Alterations in the regulatory balance may promote excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 72 publications
7
59
0
Order By: Relevance
“…Similar inhibitory actions were evoked by NPY, coreleased by neurons that contain AgRP (Broberger et al, 1998). We did not find excitatory actions of AgRP as reported in the dorsomedial VMH and PVH in rats (Davidowa et al, 2003;Li and Davidowa, 2004). Experiments with single-unit recording of unidentified cells in the VMH have suggested complex excitatory and inhibitory actions of MC3/4R agonists (Li and Davidowa, 2004).…”
Section: Agrp Also Depresses Vmh Glutamate Neurons and Does Not Antagsupporting
confidence: 77%
“…Similar inhibitory actions were evoked by NPY, coreleased by neurons that contain AgRP (Broberger et al, 1998). We did not find excitatory actions of AgRP as reported in the dorsomedial VMH and PVH in rats (Davidowa et al, 2003;Li and Davidowa, 2004). Experiments with single-unit recording of unidentified cells in the VMH have suggested complex excitatory and inhibitory actions of MC3/4R agonists (Li and Davidowa, 2004).…”
Section: Agrp Also Depresses Vmh Glutamate Neurons and Does Not Antagsupporting
confidence: 77%
“…injection of leptin (Lopez et al 2007). Thus, we cannot discard the possibility that proTRH expression reduction in this group was more probably due to ARC feeding-regulatory neuropeptides, whose effects on PVN are altered by early post-natal hyperleptinemia (Davidowa et al 2003). This hypothesis is likely given that aPVN and mPVN TRHergic neurons are innervated by axons containing a-MSH and AgRP receptors (Legradi & Lechan 1999, Fekete et al 2000; but this issue needs to be elucidated.…”
Section: Discussionmentioning
confidence: 93%
“…We can discard the inhibitory effects of NPY on TRH synthesis, since its expression in ARC was normal in the overfed group. Furthermore, altered actions of NPY on PVN neurons have been described in early-overfed animals (Davidowa et al 2003). Besides, the lack of an increase in ARC NPY expression in F-overfed rats revealed the impaired leptin signaling of this nucleus in early post-natal-overfed animals.…”
Section: Fastingmentioning
confidence: 98%
“…Several studies suggest the existence of alterations in the hypothalamic feeding-regulation systems in the perinatal overfeeding model. 11,18,40 Furthermore, it has been demonstrated that these rats are hyperleptinemic with leptin resistance to peripheral leptin. [15][16][17] In the juvenile state, after weaning, this leptin resistance to peripheral leptin is based on a specific downregulation of OB-Rb in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%